The quality of information available about Ephedra sinica on online vendor websites: The Canadian consumer experience. (March 2021) - Ng, Jeremy Y; Marwaha, Amn; Ans, Muhammad
Highlights: The DISCERN instrument was used to assess the quality of information about Ephedra sinica products on retail websites. Online retailers lacked information necessary for consumers to make informed decisions about Ephedra sinica use. The quality of information about Ephedra sinica on websites of online retailers was poor. Abstract: Background: Ephedra sinica (ES) is a natural health product used to promote weight loss, enhance athletic performance, and treat common ailments such as the common cold or flu. Due to restrictions within Canada, Canadians interested in purchasing this product turn to online vendors for the ease and discrete nature of online transactions. However, the information available on these websites for consumers looking to purchase the substance is variable. This study investigated the quality of information about ES available to Canadian consumers on the websites of these online vendors. Methods: Following searches on Google.ca, eligible websites were assessed using the DISCERN instrument, a tool consisting of 16 questions, each rated on a five-point Likert scale, to assess the quality of health information about a treatment choice. The data was used to determine the overall quality of information about ES available to consumers on these websites. Results: A total of 660 webpages were identified, of which 28 websites were found to be eligible. It was determined that the overall quality of information of websites selling ES products online was poor, as 79 % of online vendors received an average score of 2 or below. Conclusion: Consumers looking to purchase ES online are lacking critical information about this herbal product that is necessary to make an informed decision about its use. This study's findings can be used by clinicians and researchers to inform patients about the poor quality of information about ES on these websites and help them identify quality sources of information.